Indonesian Post-Orientalist Study of Islam - Ali, Muhamad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This article seeks to explain the emergence of an Indonesian post-Orientalist study of Islam from the 1990s onwards, which results from the increased influx of Indonesian-born scholars into the study of Indonesian Islam, a field previously dominated by Western-born scholars. In contrast to Edward Said’s adverse Orientalists, to the Arabic-based dirāsah islāmiyyah, and the previous generations of Indonesian Western-educated scholars, the post-1990s generation of pesantren-and-Western-educated Indonesian scholarship has taken selectively elements from Islamic texts and traditions, humanities, and social sciences in analyzing contemporary Islamic beliefs and practices. With an eclectic intellectualism combining faith and public mission, Indonesian Muslim scholars have reinterpreted Qur’anic and classical Islamic concepts while engaging different Western theories regarding religion, law, identity, and social movements. By analyzing local and national figures and movements, using diverse sources, and negotiating the tensions between the normative, practical, scriptural, and contextual, they aim to represent Islam and Muslims in their diversity and complexity in global, national, and local dynamics. With collaborative work at home and abroad, they contribute to pursuing different trajectories with scholarship and activism for Indonesian society and beyond.